The female homicide offender: serial murder and the case of Aileen Wuornos - Shipley, Stacey L. (Prentice Hall's women in criminal justice series, 2004)
Women and crime -- Women as homicide offenders -- Mental disorders in female homicide offenders -- Understanding antisocial personality disorder and psychopathy -- Understanding aspd (psychopathy) and homicide -- Attachment theory -- Methodological considerations -- Aileen Wuornos -- In search of meaning.